Entertainment for officers, noblemen, and citizens - Katalinić, Vjera (De musica disserenda, 2009)
Three representative social strata in Slavonia, Croatia organized and enjoyed secular musical theater during the nineteenth century: officers at the military fortress in Osijek, members of aristocratic families, and new wealthy citizens in Osijek. This article examines their organization, repertory, and reception.
Keywords: music; glasba; Slavonia; Slavonija; 19.st.; glasbeno gledališče; opere; operete; potujoče gledališke skupine